Smart Cane based on IoT - Faiz Abdul Ghani; Asnazulfadhli Zariman (International Journal of Education, Science, Technology, and Engineering, 2019)
Generally, blind people use a traditional cane (known as white cane) for moving from one place to another. Although, white cane is the international symbol of blindness, it could not help them to detect place and to avoid obstacles. In this paper, we represent a model of walking stick for blind people. It consists of GPS module, GPS Antenna, Arduino, ultrasonic sensor and buzzer. This stick can detect place and obstacles. Position detection part is done with GPS module and GPS antenna. Ultrasonic sensor is used for detecting obstacles. Here, the buzzer produces two types of sound. When the blind reaches to his destination, buzzer buzzes continuously. When the blind faces any obstacles, buzzer buzzes with interruption. By discovering these two types of sound, blind can be confirmed about his destination and also can avoid obstacles in front of him. The whole system is designed to be small, light and is used in conjunction with the white cane so that it could ensure safety of the blind.